A Review on the Effect of Oil or its Derivatives on Gepsious Soil - Alaa Ahmed sekhi, Hussein Abd Shaia (Mathematical Statistician and Engineering Applications, 2022)
Gypseous soils categorized as the most arduous soil because of their intricate and unforeseen behavior. Gypsum soils can be present in many parts of the world and are abundant in dry areas, and they may be close to oil pollution areas, so their geotechnical characteristics are affected by the presence of oil or its derivatives. Oil residues can be used as one of low-cost products to improve some properties of gypsum soils. It is necessary for geotechnical engineers to know the engineering properties of this type of soil as this soil is classified as collapsed, solid when it is away from water and once gypsum soil meets water it becomes weak towards high compressive forces due to the dissolution of gypsum. Because of this, many researchers have worked to find the best ways to improve this type of soil. This paper summarizes most of these previous studies related to the impact of petroleum pollution on gypsum soil, in addition to studies related to the use of petroleum materials or one of its derivatives to improve the bearing capacity of gypsum soil and reduce collapse and permeability.